The predating activity and prey impact on life cycle and development of predatory mite (amblysieus swirskii) - D, Nomindalai; D, Undarmaa (Mongolian Journal of Agricultural Sciences, 2019)
Amblyseius swirskii is commonly used to control whitefly and thrips, twospotted spider mite(T.urticae) in greenhouse vegetables and some ornamental crops. This study in each of three different types(two spotted spider mite feeding , pollen feeding, thrips feeding) of feeding pray, 1 females were observed to die at relative humidity 35-60% and at temperatures of 25-300С, laboratory light:dark(16:8) and characteristics of the pray were studied in the development of fertility. We studied mite’s nutritional features, and hunting activities. Amblysieus swirskii’s egg development good establish 2.18±0.17 days in environment which is pollen feeding, 2.48±0.04 days in thrips feeding environment, 2.014±0.098 in two spotted spider mite feeding environment, Growth is until Larvae turned to Nymph there is a hole day in three environments, until Nymph turned to adult tick there are 3.13±0.23 days in pollen feeding environment, 3.25±0.29 days in thrips feeding environment, 2.014±0.098 two spotted spider mite prey environment. A Generation 6.3±0.3 day’s pollen feeding environment, 6.72±0.25 days in thrips feeding environment, 6.55±0.32 days in two spotted spider mite prey environment. Therefore conclusion is feeding environment doesn’t influence their life cycle. Research shows that adult antelope feeds with 15.2 two spotted spider mite, 5.1 thrips daily, decreasing it`s population. Having observed the females egg development in three different types of feeding environment it showed highest result, 14 days, at a temperature of 29.7 1.47C and 30 3.33% moisture environment. In contrast it showed its lowest result, 6 days, in dusty feeding environment whereas in environment with thrips it lay it`s eggs in 12 days for an average. Observing Amblysieus swirskii’s laying egg and lifespan, found out that they able to lay 13±2.6 eggs in two spotted spider mite provision environment, 13.6±2.08 days survive. In thrips feeding environment laying 6.3±0.5 eggs and survive 12.3±2.08 days, in pollen feeding environment laying 4±1 eggs, 7.6±0.5 days surviving. Ангуучин амблисейус (аmblysieus swirskii) хачгийн идэш тэжээлийн онцлог, үржил хөгжил, ангуучлах идэвхийг судалсан дүн Хураангуй: Ангуучин хачиг амблисейус (Аmblysieus swirskii)ийн үржил хөгжлийг лабораторийн гэрэл: харанхуй (16:8), 25-300С дулаантай, 35-60% чийгшилтэй орчинд ургамлын тоос, шүлхий хачиг, трипс гэсэн гурван идэш тэжээлийн хувилбартайгаар үржил хөгжил, ангуучлах идэвхийг судлав.Ангуучин хачиг амблисейус (Аmblysieus swirskii)-ийн өндөгний хөгжил ургамлын тоос идэштэй орчинд 2.18±0.17 хоног, трипс идэштэй орчинд 2.48±0.04 хоног, шүлхий хачиг идэштэй орчинд 2.014±0.098 хоног авгалдайнаас нимф болох шатанд гурван орчинд бүгд 1 хоног, нимфээс бие гүйцсэн ангуучин хачиг болох шатанд тоос идэштэй орчинд 3.13±0.23 хоног, трипс идэштэй орчинд 3.25±0.29 хоног, энгийн шүлхий хачиг идэштэй орчинд 2.014±0.098 хоног тус тус бойжсон бол 1 үе удам нь тоосоор хооллосон орчинд 6.3±0.3 хоног, трипсээр хооллосон орчинд 6.72±0.25 хоног, энгийн шүлхий хачгаар хооллосон орчинд 6.55±0.32 хоног тус тус үргэлжлэв. Ангуучин бие гүйцсэн амблисейус (Аmblysieus swirskii) хачгийн ангуучлах идэвхийг судлахад өдөрт 15.2 шүлхий хачиг, 5.1 трипс дунджаар идэж тоо, толгойг бууруулж байна. Эмэгчин хачгийн төлөрхөг чанарыг дээр дурьдсан гурван идэш тэжээлийн орчинд судлахад шүлхий хачиг идэш тэжээлийн орчинд хамгийн олон хоног өндөглөсөн буюу дунджаар 14 хоног, хамгийн цөөн хоног өндөглөсөн буюу тоостой идэш тэжээлийн орчинд дунджаар 6 хоног өндөглөсөн бол трипстэй идэш тэжээлийн орчинд дунджаар 12 хоногийн турш өндөглөлт үргэжилж байна. Ангуучин хачгийн өндөглөлт ба амьдрах хугацааг тогтооход энгийн шүлхий хачиг идэш тэжээлийн орчинд 13±2.6 өндөг төрүүлж, 13.6±2.08 хоног амьдарч, трипс идэш тэжээлийн орчинд 6.3±0.5 өндөг гаргаж 12.3±2.08 хоног амьдаржилж басан бол тоостой идэш тэжээлийн орчинд 4±1 өндөг гаргаж 7.6±0.5 хоног тус тус амьдарч байгааг тогтоов. Түлхүүр үг: Биологийн хамгаалал, ангуучлах идэвх, идэш тэжээлийн онцлог